(untitled) (Eureka Journal of Computing Science & Digital Innovation, 2026)
Artificial Intelligence (AI) technologies are currently driving significant transformations in the labor market. They enhance efficiency by automating and optimizing production processes; however, they also contribute to the disappearance of traditional occupations and the emergence of new ones. This article analyzes the impact of AI on the labor market, examining its economic and social consequences. Particular attention is given to the distribution of jobs, the growing demand for new skills, and issues of social equality. Furthermore, the study addresses labor rights, the importance of education and upskilling, as well as the role of governments and international organizations in regulating AI. The paper emphasizes the necessity of developing new economic and social paradigms in response to the expanding influence of AI technologies.